COVID-19 AND MACROECONOMICS: IS IT REALLY MATTER IN ISLAMIC BANK FINANCING? EVIDENCE FROM INDONESIA - Syafa’ati, Anggun Azmi Nur; Wicaksono, Ahmad Tibrizi Soni (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
This study aims to determine the effect of COVID-19, economic growth and inflation partially and simultaneously on Islamic bank financing in Indonesia. The type of this research is quantitative using dummy variables. The population taken is Islamic commercial bank financing in Indonesia using the saturated sampling method as a research sample. The data used is secondary data and the data collection method is by accessing the annual financial statements for the period January 2015 - December 2022 on the official website of the Financial Services Authority (OJK). The analysis method used is dummy regression analysis. The results showed that the COVID-19 pandemic and GDP had a positive and significant effect on Islamic Bank financing in Indonesia, while inflation partially had no significant effect on Islamic bank financing in Indonesia. Meanwhile, simultaneously COVID-19, Inflation and GDP have a significant effect on Islamic bank financing in Indonesia.